An integrated subacute stroke ward within a community hospital increases rehabilitation efficiency and reduces healthcare expenditure - San San Tay; Teck Kheng Edward Goh; Mon Hnin Tun; Edmund Jin Rui Neo; Onn Kei Angel Lee (Proceedings of Singapore Healthcare)
Background Stroke is a leading cause of hospitalisation, disability, and death in Singapore. The healthcare system’s rehabilitative care model has seen ongoing evolution in response to changing patient needs and healthcare financing demands. Changi General Hospital (CGH) and St Andrew’s Community Hospital (SACH) collaborated on an integrated subacute stroke ward (SSW) in 2019 to optimise the transfer of stroke patients to the subacute rehabilitation setting. Objective To evaluate the outcomes of the integrated SSW. Methods This was a retrospective study. Anonymised data was used to evaluate functional, financial, and length-of-stay (LOS) outcomes. Results There were 71 patients in the control group (historical cohort) and 226 patients in the SSW cohort. Both groups were demographically, medically, and functionally similar except for a higher proportion of lacunar infarcts (LACI) in the SSW group. Although functional scores by Modified Barthel Index (MBI) were similar on discharge, the total LOS fell significantly (20 days) for the SSW group, with significant improvements in median rehabilitation efficiency (19.6 vs 10.9) but not median rehabilitation effectiveness (35.3 vs 31.0). Subgroup analysis revealed no impact from the disproportionate number of LACIs. Gross bill size, when corrected for inflation, was significantly lower across the combined hospitalisation ($31,270 vs $40,005). Conclusions This collaboration achieved savings in healthcare expenditure and LOS without compromising functional outcomes. The community hospital is a potent bridge for care transition and integrated services such as the SSW can optimise the rehabilitation journey for patients with stroke. Innovation in care provision can help to address the ever-changing challenges of healthcare.